A Case of Sublingual Ranula That Responded Successfully to Localized Injection Treatment with OK-432 after Healing from Drug Induced Hypersensitivity Syndrome - Kunio Yoshizawa; Akinori Moroi; Shuichi Kawashiri; Koichiro Ueki (Hindawi Limited, 2016)
A ranula is a mucus retention cyst or pseudocyst caused by leakage of mucus from the sublingual gland and generally occurs in the oral floor. In addition, drug induced hypersensitivity syndrome (DIHS) is a rare but well-recognized serious adverse effect characterized by fever, skin rashes, generalized lymphadenopathy, hepatitis, and hepatosplenomegaly and oral stomatitis. This paper presents the first case of successfully treated sublingual ranula with localized injection of OK-432 after healing from drug induced hypersensitivity syndrome, which has previously been unreported in the literature. We present the case of a 38-year-old Japanese woman with sublingual ranula that responded successfully to localized injection treatment with OK-432 after healing from drug induced hypersensitivity syndrome. She was affected with cutaneous myositis and interstitial lung disease when she was 26 years old. At the age 34 years, she received additional oral treatment of diaminodiphenyl-sulfone due to deterioration of the cutaneous myositis, which resulted in drug induced hypersensitivity syndrome (DIHS) with severe oral stomatitis. Local injection of OK-432 to the ranula may be a very safe and useful treatment method even if the patient has a history of drug allergy and has connective tissue disease such as cutaneous myositis.